Manuel Alcántara Sáez y Juan Manuel Ibeas Miguel (eds.). Colombia, ante los retos del siglo XXI: desarrollo, democracia y paz. Salamanca, Ediciones Universidad, 2001 - Guzmán Mendoza, Carlos Enrique (Estudios Políticos, 2002)
Reseña